Characteristics and Potential of Placer Gold Deposit in Lakan Bilem Block, West Kutai District, East Kalimantan, Indonesia - Arifudin Idrus; Ni’matul Azizah Raharjanti; Sufriadin (Journal of Geoscience, Engineering, Environment, and Technology, 2022)
Kalimantan is recognized as one of Indonesian islands with huge prospect of minerals particularly gold both primary and secondary deposit styles. However, the publication of the gold resources is still restricted to be described in regional/district scale maps or exploration company internal reports, hence, a detailed study on deposit scale remains limited. This study is aimed to document the characteristics and the estimation of potential or resources of the secondary (placer) gold deposit in Lakan Bilem block, West Kutai district, East Kalimantan province, Indonesia. The study was done by field observation followed by microscopic analysis and simple resources estimation of the gold. Gold in the study area occur in the semi-consolidated paleo alluvial deposit as trace mineral. The gold morphologies show platy to angular form with coarse surface which indicates the process of gold deposition is predominantly controlled by hydrodynamic transportation at a relatively moderate regime. Estimation of the indicated resources of gold results a total of 4.96 tonnes of gold potentially occurred in the study area. Exploration drilling with 100 spacing grid is suggested to delineate lateral and vertical distribution of the gold deposit. The drilling also will upgrade confidence level of the resources from indicated to measured resources.